Using single-operator cholangioscopy for endoscopic evaluation of indeterminate biliary strictures: results from a large multinational registry - Almadi, Majid A.; Itoi, Takao; Moon, Jong Ho; Goenka, Mahesh K.; Seo, Dong Wan; Rerknimitr, Rungsun; Lau, James Y.; Maydeo, Amit P.; Lee, Jong Kyun; Nguyen, Nam Q.; Niaz, Saad K.; Sud, Randhir; Ang, Tiing Leong; Aljebreen, Abdulrahman; Devereaux, Benedict M.; Kochhar, Rakesh; Reichenberger, Jörg; Yasuda, Ichiro; Kaffes, Arthur J.; Kitano, Masayuki; Peetermans, Joyce; Goswamy, Pooja G.; Rousseau, Matthew J.; Reddy, D. Nageshwar; Lakhtakia, Sundeep; Lee, Yun Nah; Rai, Vijay Kumar; Kamada, Kentaro; Tanaka, Reina; Tonozuka, Ryosuke; Tsuchida, Akihiko; Song, Tae Jun; Ramchandani, Mohan K.; and the SpyGlass AMEA Registry Group (Endoscopy, 2020)
Background Peroral cholangioscopy (POCS) of indeterminate biliary strictures aims to achieve a diagnosis through visual examination and/or by obtaining targeted biopsies under direct visualization. In this large, prospective, multinational, real-life experience of POCS-guided evaluation of indeterminate biliary strictures, we evaluated the performance of POCS in this difficult-to-manage patient population.Methods This prospective registry enrolled patients, with indeterminate biliary strictures across 20 centers in Asia, the Middle East, and Africa. The primary end points were the ability to visualize the lesion, obtain histological sampling when intended, and an assessment of the diagnostic accuracy of POCS for malignant strictures. Patients were followed for 6 months after POCS or until a definitive malignant diagnosis was made, whichever occurred first.Results 289 patients underwent 290 POCS procedures with intent to biopsy in 182 cases. The stricture/filling defect was successfully visualized in 286/290 (98.6 %), providing a visual diagnostic impression in 253/290 (87.2 %) and obtaining adequate biopsies in 169/182 (92.9 %). Procedure-related adverse events occurred in 5/289 patients (1.7 %). POCS influenced patient management principally by elucidating filling defects or the causes of bile duct stricture or dilation. The visual impression of malignancy showed 86.7 % sensitivity, 71.2 % specificity, 65.8 % positive and 89.4 % negative predictive value, and 77.2 % overall accuracy compared with final diagnosis. Histological POCS-guided samples showed 75.3 % sensitivity, 100 % specificity, 100 % positive and 77.1 % negative predictive value, and 86.5 % overall accuracy.Conclusion In this large, real-life, prospective series, POCS was demonstrated to be an effective and safe intervention guiding the management of patients with indeterminate biliary strictures.